Resource curse, economic efficiency and green recovery based on three-subject framework - Gao, Shiya; Guan, Xin; Tang, Run; Zhu, Junfan; Wang, Zeyu; Xu, Wei (Resources policy, 2023)
We examine the effects of environmental resources policy on enterprises total factor productivity (TFP), based on data of manufacturing companies from 2008 to 2017 and a three-subject framework of central government, local governments, and enterprises. A difference-in-differences assessment strategy is constructed using China's new environmental protection law as a quasi-natural experiment for the regulatory environment. The results show that the new Environmental Protection Law can promote enterprises TFP. And after performing multiple robustness tests, the results remain significant. We then explore the heterogeneous effects of enterprise political resources and find that there is a “political resource curse” effect in Porter hypothesis, i.e. stringent environmental regulations cannot promote the TFP of enterprises with political resources. Local government political connections may have led to a “political resource curse” effect, rather than central government. This article accordingly proposes targeted policy recommendations to improve the total factor productivity of enterprises and promote national economic development. •The resource curse play a role in resource allocation in the green economic market.•The implementation of new Environmental Protection Law can significantly improve highly polluting enterprises' TFP.•Political resources may decrease the impact of environmental regulations and inhibit enterprises' TFP.